Comparative study of photodegration of orange by solar and fenton process / Wan Abdul Rahim Wan Musa - Wan Musa, Wan Abdul Rahim (Faculty of Applied Sciences, 2017)
Wastewater is exhausted in large volume every year due to the processes of textile industries such as dyeing am finishing processes. Nowadays, more than 50% of dyes used in textile industry are Azo-based dyes. Inorganic salts improve the coloration of the dye, which enhances the pollution load of wastewater from textile industries. Degradation of the reactive textile dye Orange Gelb (OG) was studied using Fenton's Reagent of Advanced Oxidation Processes (AOPs) and solar photo catalytic by TiO2. A laboratory set-up was designed to evaluate the effectiveness for both treatment. The initial concentration of OG in the reaction was 5 ppm. The effects of irradiation time and the condition of pH dye and concentrations of catalyst (TiO2, H2O2 and FeSO4) on the degree of degradation efficiency were studied. The results indicated that photo-Fenton's process is more effective than solar photo degradation by TiO2. The degradation effectiveness of Fenton's procedure was up to 79.22% in 2 hour rate at pH 3 and in 3.1 X 10-2 M, while the degradation efficiency of TiO2 was just up 19.75% at pH6 am in 5 ppm The degradation effectiveness of Fenton process increased as the concentration of OG dye decreased, the concentration of H202 increased, concentration of FeSO4 increased and pH value get decreased which is in more acidic. While for photo degradation for TiO2, the best degradation happened when TiO2 concentration increased, concentration of OG dye decreased, and ph value increased.